Quantum Mechnical/Molecular Mechanical Simulations of the Hydride Transfer Reactions in Quinone Reductase 2 - Reinhardt, Clorice (My University, 2015)
The purpose of this study was to examine the effect of the protein matrix on the energetics of the hydride transfer reaction, as well as understanding the role of the aromatic side chains on the hydride transfer reaction.
Color poster with text, images, charts, tables, and graphs.
Keywords: Chemistry; Kinetics; Quinone reductases (QR); Posters